An Economic Incentive for D2D Assisted Offloading Using Stackelberg Game - Yanan Qiao; Ying Li; Jianbo Li (IEEE Access, 2020)
The explosive growth of traffic demand challenges the current cellular network. Device-to-Device assisted offloading is a promising solution for alleviating traffic overloading burdens. However, a content transmitter (CT) unwillingly participates in cellular offloading due to the selfish nature and non-cooperation. To this end, an incentive mechanism initiated by mobile users (MUs) is proposed to motivate the CT's participation for maximizing the CT's profit and mobile users' utilities. In particular, we consider the utility of a mobile user by jointly combining effects of social awareness and network congestion. The MUs and content providers offer proper economic payments to compensate the CT's energy consumption cost. The interactions among participants formulate a two-stage Stackelberg game. The main aim of this game is to reach Nash equilibrium (NE) that neither the CT nor MUs have incentives to deviate unilaterally. We theoretically prove the existence and uniqueness of NE. Furthermore, iterative algorithms are designed to calculate NE for obtaining the best strategies of the CT and MUs. Numerical results demonstrate the robustness and feasibility of our proposed model.